Cost-consequence analysis of sitagliptin versus sulfonylureas as add-on therapy for the treatment of diabetic patients in Italy - Lorenzoni V; Baccetti F; Genovese S; Torre E; Turchetti G (Dove Medical Press, 2017)
Valentina Lorenzoni,1 Fabio Baccetti,2 Stefano Genovese,3 Enrico Torre,4 Giuseppe Turchetti1 1Institute of Management, Scuola Superiore Sant’Anna, Pisa, Italy; 2SD Diabetology, ASL Toscana Nordovest, Massa Carrara, Italy; 3Cardiovascular and Metabolic Department, IRCCS Multimedica Sesto San Giovanni, Milan, Italy; 4SSD Endocrinologia, Diabetologia e Malattie metaboliche, ASL 3 Genovese, Genoa, Italy Objective: Diabetes mellitus is a chronic disease related to a significant impact in both epidemiologic and economic terms. In Italy, around 3.6 million people are affected by diabetes and this number is expected to increase significantly in the next few years. As recommended by current national and international guidelines, metformin (Met) is prescribed as first-line pharmacological treatment, and many pharmacological alternatives are available for patients uncontrolled with Met monotherapy. Despite the availability of many innovative oral antidiabetic drugs (OADs), such as dipeptidyl peptidase 4 inhibitors (DPP4-i) and its first-in-class sitagliptin (SITA), which entered the Italian market in the last 10 years, their usage is consistently lower than traditional drugs such as sulfonylureas (SUs). In fact, due to higher acquisition costs, the prescription of innovative OADs in Italy is restricted to specialist, resulting in a prominent usage of traditional OAD that can be prescribed also by general practitioners (GPs). A cost consequence analysis (CCA) was performed in order to compare SITA with SU, as second-line therapy in add-on to Met, in terms of costs and related clinical events over 36 months.Methods: A CCA was conducted on a hypothetical cohort of 100,000 type 2 diabetes mellitus (T2DM) patients uncontrolled with Met monotherapy, from both the Italian National Health Service (INHS) and societal perspective. Therefore, both direct (drugs, self-monitoring, hypoglycemia, major cardiovascular events [MACEs], and switch to insulin) and indirect costs (expressed in terms of productivity losses) were evaluated. Clinical and economic data were collected through Italian national tariffs, literature, and experts’ opinions. Three expert clinicians finally validated data inputs. To assess robustness of base case results, a one-way sensitivity analysis (OWSA) and a conservative scenario analysis – excluding MACEs – were carried out.Results: In the base case analysis, the higher drug costs related to SITA were offset by other management costs (ie, lower use of devices for glycemia self-monitoring, lower incidence of hypoglycemia and MACE, and delay to insulin switch). As a result, the economic evaluation showed that, compared to SU, SITA was cost saving from both societal (–€61,217,723) and INHS (–€51,846,442) perspectives over 3 years as add-on to Met. The base case results were also confirmed by the scenario analysis and by the OWSA performed on the key parameters. The adoption of SITA, in a cohort of 100,000 diabetes patients, would avoid 26,882 non-severe hypoglycemic events, 6,528 severe hypoglycemic events, and 1,562 MACEs.Conclusion: This analysis suggests that, compared to SU, SITA could be a sustainable and cost-saving alternative for the management of T2DM patients uncontrolled with Met monotherapy from both clinical and economic perspectives. Keywords: diabetes, dipeptidyl peptidase 4 inhibitors, sitagliptin, sulfonylurea, cost-consequence analysis